DAMPAK MEDIA VIDEO PEMBELAJARAN INTERAKTIF BERBASIS RME TERHADAP PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR DI PURWAKARTA - Anggi Y. Anggraeni; Yudi Bachtiar; Annisa Nurfitriani (STKIP Subang, 2026)
Mathematical understanding is essential in elementary mathematics learning, but students may still struggle to understand concepts and apply them to contextual problems. This study examined differences and improvement in mathematical understanding and the impact of RME-based interactive learning video media on solid geometry learning for fifth-grade students in Purwakarta. A quantitative quasi-experimental study with a nonequivalent control group design was conducted with 28 students: 14 in the experimental group and 14 in the control group. Data were collected through pretests and posttests and analyzed using t-tests and N-Gain. The experimental mean increased from 47.86 to 77.86 with an N-Gain of 0.558 (moderate), while the control group obtained 0.091 (low). The posttest difference was significant (t = 5.779, p < .05), and the N-Gain comparison was also significant (t = 3.987, p = .001). The findings indicate that RME-based interactive learning video media positively and significantly improved students’ mathematical understanding.